Effect of Exponential Averaging on the Variability of a RED Queue - MISRA, Archan (Institutional Knowledge at Singapore Management University, 2001)
The paper analyzes how using a longer memory of the past queue occupancy in computing the average queue occupancy affects the stability and variability of a RED queue. Extensive simulation studies with both persistent and Web TCP sources are used to study the variance of the RED queue as a function of the memory of the averaging process. Our results show that there is very little performance improvement (and in fact, possibly significant performance degradation) if the length of memory is increased beyond a very small value. Contrary to current practice, our results show that a longer memory reduces the negative correlation typically observed among the windows of the constituent TCP flows, and hence, suggest the use of the instantaneous queue occupancy in practical RED queues